Identification and analysis of differentially expressed (DE) circRNA in epididymis of yak and cattleyak - Li, Chunhai; Yan, Yan; Pan, Cheng; Adjei, Michael; Shahzad, Khuram; Wang, Peng; Pan, Meilan; Li, Kerui; Wang, Ye; Zhao, Wangsheng (Frontiers in Veterinary Science, 2023)
Circular RNAs (circRNAs), as endogenous non-coding RNA with unique closed ring structure, is closely related to animal reproduction, and understanding the expression of circRNA in yak and cattleyak epididymal tissues is of great significance for understanding cattleyak sterility. Based on this, we screened and identified the differentially expressed circRNA in the epididymis of three yaks and two cattleyak. A total of 1,298 circRNAs were identified in the epididymis of yak and cattleyak, of which 137 differentially expressed (DE) circRNAs and the functions of some of them were elucidated in this research, as well as qPCR verification to 6 circRNAs from the 137 DE circRNAs. Gene Ontology (GO) enrichment analysis suggested that DE circRNAs were mainly related to metabolic process, development process, immune system process, reproductive process, reproduction, biological adhesion and growth. COG classification analysis showed that the DE circRNAs derived genes were mainly related to replication, recombination and repair. KEGG pathway analysis suggested that DE circRNAs were mainly involved in RNA degradation. In addition, we also screened Bta-mir-103, which is a circRNA binding miRNA related to sperm activity.